The Influence of System Knowledge, Coworker Support, and System Usage Frequency on the Effectiveness of Computerized Financial Reporting with Trust in the System as a Moderating Variable - Tengku Sheila Chairunisa; Renny Maisyarah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine and analyze, both partially and simultaneously, the influence of system knowledge, coworker support, and frequency of system usage on the effectiveness of computerized financial reporting and trust in the system. Furthermore, this research investigates the moderating role of trust in the system in the relationship between those three independent variables and reporting effectiveness. This study is considered novel as it incorporates three variables not previously explored in combination—particularly trust in the system as a moderating factor. The study was conducted on 391,500 employees from 94 banks across Indonesia, with a sample of 100 employees selected using Slovin’s formula. The independent variables in this research are system knowledge, coworker support, and frequency of system usage; the dependent variable is the effectiveness of computerized financial reporting; and the moderating variable is trust in the system. A quantitative descriptive approach was employed, and data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings reveal that system knowledge, coworker support, and frequency of system usage each significantly affect both computerized financial reporting effectiveness and trust in the system. Trust in the system is also found to significantly impact the effectiveness of computerized financial reporting. Simultaneously, only system knowledge and usage frequency show a significant effect when trust in the system serves as a moderating variable, whereas coworker support does not exert a significant influence under the same condition.